Compósitos com interfaces autorreparáveis de poli(metacrilato de metila) (PMMA) contendo fibras de carbono decoradas com pontos quânticos de carbono - Érica Correia Duarte (2020)
Fiber-polymer matrix interfacial debonding is often observed when mechanical loads are applied to fiber reinforced polymer composites. These defects usually end-up leading to a catastrophic fracture of the composites. In this work, we tested the hypothesis that interfaces in polymer composites could be designed and created to display self-healing abilities, so they could recover from any eventual damage and be able to withstand new mechanical loadings. The proposed self-repair methodology is the addition of carbon quantum dots, the carbon dots (CD), dispersed on the surface of carbon fibers (CF) chemically treated by an immersion method. These decorated fibers were then incorpo-rated into poly(methyl methacrylate) (PMMA) by the compression molding method, when the carbon fiber meshes were used, and by the high intensity mixer method with chopped carbon fibers. CDs with diameters of 10 nm (by TEM) and functional groups (by CHN and FTIR), such as amine and carboxylic groups were successfully synthe-sized by the microwave pyrolysis method. The deposition of CD on the surface of CF was evaluated and quantified by UV-vis spectroscopy and 1.2wt.% of CD on CF was determined. AFM images of the surface of the carbon fibers showed a difference in roughness between the treated fibers. Composites with different surface treatments (in-cluding the presence of CD) did not show significant differences in strength, stiffness and damping, suggesting that the surface treatments on CF did not lead to major chang-es in the degree of interfacial interaction. Self-healing tests showed that damaged com-posites with CD decorated CF were able to restore their original properties, while no self-healing effect was noted in composites with no CD on CF. The observed self-healing behavior between PMMA and CF decorated with CD is due to the interactions between chemical groups on the surface of the CD and PMMA. Thus, damages related to fiber-matrix interfacial detachments can be repaired through reversible interactions based on CD.